Proceedings of the 12th International Workshop on Variability Modelling of Software-Intensive Systems 2018
DOI: 10.1145/3168365.3168371
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Better Understanding of Software Features and Their Characteristics

Abstract: The notion of features is commonly used to describe, structure, and communicate the functionalities of a system. Unfortunately, features and their locations in software artifacts are rarely made explicit and often need to be recovered by developers. To this end, researchers have conceived automated feature-location techniques. However, their accuracy is generally low, and they mostly rely on few information sources, disregarding the richness of modern projects. To improve such techniques, we need to improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…It is not completely clear, however, how these syntactic code extensions, which aim at realizing configurability, relate to semantic code extensions, that is, units of functionality from a domain-oriented view. Understanding this relationship constitutes an interesting future research question [44].…”
Section: Likert−scale Responsementioning
confidence: 99%
See 1 more Smart Citation
“…It is not completely clear, however, how these syntactic code extensions, which aim at realizing configurability, relate to semantic code extensions, that is, units of functionality from a domain-oriented view. Understanding this relationship constitutes an interesting future research question [44].…”
Section: Likert−scale Responsementioning
confidence: 99%
“…To avoid feature-location efforts, researchers have proposed to use embedded annotations to record feature locations directly in the code (similar to ifdefs) together with respective tooling and case studies [56][57][58][59]. Notably, Krüger et al [44] manually annotated feature locations of mandatory features in the open-source 3d printer firmware Marlin and found that their code-level characteristics differ from optional features. Specifically, mandatory features are less scattered, probably since they align better with the software architecture.…”
Section: Related Workmentioning
confidence: 99%
“…to record and later analyze variability decisions (railway, imaging technology, and traffic control case), such as rationales for introducing variability. It was also stated that recording information about refactorings would be helpful, preferably using embedded annotations (Ji et al 2015;Andam et al 2017;Abukwaik et al 2018;Seiler and Paech 2017;Krueger et al 2018aKrueger et al , 2019a. The recording should explicitly relate refactorings to either the introduction of new functionality (features) or to maintenance.…”
Section: Record and Analyze Variability Decisions Several Of Our Casementioning
confidence: 99%
“…As such, a feature modeling process is needed, that supports obtaining a feature model from a diverse set of variability information sources (Bécan et al 2016;Davril et al 2013;Krueger et al 2019a), integrated with feature-model management, merging, and synthesis techniques (Acher et al 2010, b, She et al 2011. Our cases express that functional evolution is well reflected in commit messages (e.g., bug fix information, new feature implementations, new branches), which confirms some insights that commit messages are a good source for feature identification (Krueger et al 2018a(Krueger et al , 2019aZhou et al 2018).…”
Section: Feature-modeling Processmentioning
confidence: 99%
See 1 more Smart Citation